Peningkatan Hasil Belajar Peserta Didik Menggunakan Model Discovery Learning pada Pembelajaran Tematik Terpadu di Sekolah Dasar - Jeliana Jeliana; Muhammadi Muhammadi (Universitas Negeri Padang, 2023)
The problem in this research is motivated by the low learning outcomes of students. The purpose of this study was to describe the increase in student learning outcomes using the Discovery Learning model in integrated thematic learning in class V UPT SDN 08 Pasar Surantih, Pesisir Selatan District. This research is a classroom action research with a quantitative and qualitative approach with four stages, namely planning, implementing, observing, and reflecting. The research subjects were teachers and students of class V UPT SDN 08 Pasar Surantih and carried out in two cycles. The results showed that the observation of lesson plans for cycle I averaged 86.11% (B) and increased in cycle II with a percentage of 94.44% (SB), in cycle I teacher activity an average of 82.81% (B) increased in cycle II with a percentage of 94.44% (SB), in the activity of students in cycle I an average of 82.81% (B) increased in cycle II with a percentage of 94.44% (SB) and student learning outcomes in cycle I averaged average 71.67 (C) increased in cycle II 86.05 (B). Thus, integrated thematic learning using the Discovery Learning model can improve learning outcomes in class V UPT SDN SDN 08 Pasar Surantih, Pesisir Selatan Regency.